2023
DOI: 10.1093/carcin/bgad091
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biomarkers for the early detection of non-small cell lung cancer: a systematic review and meta-analysis

Eithar Mohamed,
Daniel J García Martínez,
Mohammad-Salar Hosseini
et al.

Abstract: Lung cancer (LC) causes few symptoms in the earliest stages, leading to one of the highest mortality rates among cancers. Low-dose computerised tomography (LDCT) is used to screen high-risk individuals, reducing the mortality rate by 20%. However, LDCT results in a high number of false positives and is associated with unnecessary follow-up and cost. Biomarkers with high sensitivities and specificities could assist in the early detection of LC, especially in patients with high-risk features. Carcinoembryonic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 140 publications
0
7
0
Order By: Relevance
“…Tumour antigens have been investigated as biomarkers for the early diagnosis of LC [100], but most have low sensitivity and specificity, and are more accurate at identifying advanced disease. Further research will need to engage advanced methodologies to identify protein signatures associated with the specific cancer type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumour antigens have been investigated as biomarkers for the early diagnosis of LC [100], but most have low sensitivity and specificity, and are more accurate at identifying advanced disease. Further research will need to engage advanced methodologies to identify protein signatures associated with the specific cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…We recently used the Preferred Reporting Items for Systematic Review (PRISMA) guidelines [98,99] to perform a systematic review of the literature [100] to address the research question -what are the most promising biomarkers for an early diagnosis of LC? The protocol was registered with PROSPERO (CRD42022336488) and we screened seven literature databases (CINAHL, MEDLINE, PubMed, Scopus, Web of Science, Cochrane library and Clinicaltrial.gov) from 1 January 1970 until 21st May 2023 using the following MeSH terms (cancer* or tumor* or tumour* or neoplasm* or carcinoma* or malignancy*) AND (lung* or pulmonary) AND (antigen* OR protein* OR RNA* OR ctDNA* OR miRNA* OR cell surface marker* OR inflammatory cell*) AND (early detection OR early diagnosis OR early biomarker OR early marker).…”
Section: The State-of-the-artmentioning
confidence: 99%
“…Biomarkers can be useful tools to evaluate effective treatment, monitor for disease recurrence after therapy, and enable prognostic prediction. miRNAs combined with autoantibodies/TAAs may aid in detecting early NSCLC [17], as the early stages have better survival rates and assist in decreasing the associated costs of the healthcare system.…”
Section: Tumour Antigens As Biomarkers For Lcmentioning
confidence: 99%
“…We recently used the Preferred Reporting Items for Systematic Review (PRISMA) guidelines [37,38] to perform a systematic review of the literature [17] We identified 98 articles that focused on the identification and assessment of diagnostic biomarkers and achieved a pooled AUC of 0.85 (95% CI 0.82-0.088), indicating that the diagnostic performance of these biomarkers when combined was excellent. However, the heterogeneity was also considerable (I 2 = 98%, p < 0.00001).…”
Section: The Potential Of Biomarker Panels For Lc Detectionmentioning
confidence: 99%
“…Since tumor cells are transformed from normal cells, biomarkers are an objective assessment for the early detection of tumors. Some circulating antigens such as CYFRA21-1, CEA, NSE, and SCC-Ag have been used as markers for the clinical detection of lung cancer ( 7 , 8 ) ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%